Text Analysis Extraction and Text Representation - Ojo, Adebola K. (Text Mining Techniques with Applications, Edition 1, 2024)
We will discuss the categories of how texts are extracted and how to represent these unstructured text documents with appropriate format and structure to support later automated text mining algorithms.